The Use Of New Media Habits For Muhammadiyah Bantul High School Students To Access Religious Information And Disaster - Ishak, Aswad (2015)
The new media has now entered a wide variety of life. The presence of gadgets with different brands more easily and cheaply obtained. Almost every individual has gadgets like mobile phones. Technological devices is largely now has the ability connected internet access. The use of these gadgets are not the same from one person to another, as well as the existing generation. Generation gap between parents and teens is a logical consequence in the use of communication media in everyday life. Teens today, as the digital generation, has a unique and distinctive way in consuming new media.